Students’ Satisfaction on Learning Contents, Process and Effects of ED6043 Educational Research Course at Graduate School of Education, Assumption University: A Classroom Research Study - YE, YAN (Scholar: Human Sciences, 2014)
This study was a classroom research project, which investigated of the teaching effects of ED6043 Educational Research course on student learning for the purpose of improving instruction. The research aimed to identify the students’ perception towards the learning contents of ED6043 course firstly; then to determine their satisfaction towards the teaching and learning process of ED6043 course, and lastly to measure to what extent that ED6043 course helps students to do their thesis or independent study in the real practices. The research used descriptive statistics, including frequency, percentage, means and standard division to do with the data. 66 students who finished studying ED6043 course completed the survey and the results revealed that: More than half (61%) of the students didn’t know anything about the educational research. “Research planning: find a research problem, write research questions, and objectives” and “Review of Fundamental Statistics” were regarded as the hardest contents of ED 6043 course. The most helpful contents of ED 6043 course were: How to Prepare for the proposal /final defense, and how to write chapter 1; meanwhile, though “Research planning: find a research problem, write research questions, and objectives” and “Review of Fundamental Statistics” were regarded as the hardest contents of ED 6043 course, they are also greatly helpful contents in the students’ perceptions. Students eager to learn “Review of Fundamental Statistics” more. The means of students’ satisfaction towards the course was 4.1864, which showed most students were quite satisfied with the present teaching and learning of the course. Students agreed that this course to some extent helped them quite much to do their own thesis, independent study and future research. Findings were reviewed and recommendations practical recommendations concentrated on how to arrange the learning contents and process more effectively and improving the learning effectiveness through more peer learning and case studies.